2014
DOI: 10.1371/journal.pone.0096874
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Examine the Correlation between Cognition and Blood Biomarkers in a Singapore Chinese Male Cohort with Type 2 Diabetes Mellitus

Abstract: BackgroundDiabetes is reported to be linked to poorer cognitive function. The purpose of this study is to examine (a) clinical correlation between cognitive function and the biochemical perturbations in T2DM, and (b) the impact of statin treatment on cognitive function in diabetic subjects.MethodsForty Singaporean Chinese males with diabetes and twenty Singaporean Chinese males without diabetes were recruited for this study. Twenty-two of the diabetic subjects were on statin therapy and all subjects were non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…A possible explanation for this difference may be the ages of the patients included in the analyses, as the patients in our study were relatively young. For example, the estimated prevalence of CI among patients ≥ 65 years old is 7% in Mexico and may vary between 3% and 5.9% in Latin America [ 30 ]; and the relatively low prevalence of CI noted among the patients with T2D in our study is consistent with the results of studies analyzing younger patient cohorts [ 31 ]. However, the prevalence noted in the present study was higher than expected for a group of patients with an average age of 50 years.…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation for this difference may be the ages of the patients included in the analyses, as the patients in our study were relatively young. For example, the estimated prevalence of CI among patients ≥ 65 years old is 7% in Mexico and may vary between 3% and 5.9% in Latin America [ 30 ]; and the relatively low prevalence of CI noted among the patients with T2D in our study is consistent with the results of studies analyzing younger patient cohorts [ 31 ]. However, the prevalence noted in the present study was higher than expected for a group of patients with an average age of 50 years.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that serum HDL‐C is specifically associated with executive function in older people with diabetes mellitus. A case–control study found a positive association between HDL‐C levels and executive function in the diabetic statin users, but not in non‐users. A longitudinal study in France reported that lower HDL‐C was associated with an increased risk of cognitive decline in executive function and psychomotor speed in older men.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these studies that used a single test to assess executive function, we measured executive function from a composite of two tests. Another study showed no differences in cognitive measures in diabetic and non-diabetic controls, however, diabetic statin users had worse performance on tests of executive function, suggesting potentially worse vascular disease that could impact executive function [34]. Previous reports on neuropsychological testing in DM versus non-DM have varied from comparisons of a single test [35, 36] to a comprehensive battery [3739].…”
Section: Discussionmentioning
confidence: 99%